Delivering Policy Reform - Lindquist, A.; Vincent, Sam; Wanna, John (ANU Press, 2011)
Predictable and unpredictable challenges continually confront the policy settings and policy frameworks of governments. They provide a constantly changing dynamic within which policy-making operates. Governments at all levels are asking their public services to identify innovative and workable reforms to anticipate and address these challenges. Public service leaders around the world are struggling not only to better anticipate emerging demands but also to address reform backlogs. However, time and time again, major policy reforms can prove tough to implement - especially in turbulent environments - and even tougher to anchor over time. This leads to considerable uncertainty and inefficiency as governments and policy communities try to keep pace with change. Policies that unravel or are dismantled are costly and represent wasted opportunities. They lead to cynicism about the effectiveness of governments and public service advice more generally, making it more difficult to deal with other emerging challenges. This volume of proactive essays on delivering policy reform offers an intriguing blend of strategic policy advice and management insight. It brings together a diverse range of highquality contributors from overseas as well as from Australia and New Zealand - including national political leaders, public service executives, heads of independent agencies, and leading international scholars.